Interaction between the systemic immune-inflammation index and trouble sleeping in nonalcoholic fatty liver disease: a cross-sectional study of the NHANES 2005-2018 data - Xinxia Yang; Shitu Zhuo; Huie Zhuang; Taiyong Fang (BMC, 2024)
Abstract Background The systemic immune-inflammation index (SII) and trouble sleeping are independent risk factors for nonalcoholic fatty liver disease (NAFLD). Nevertheless, studies investigating the combined effects of the SII and troubled sleeping on NAFLD are lacking. In this study, we investigated the independent relationships and interactions between trouble sleeping and the SII among patients with NAFLD. Methods Data from seven survey cycles of the National Health and Nutrition Examination Survey (NHANES) (2005-2018) were analyzed. The SII was obtained by counting platelets, neutrophils, and lymphocytes. NAFLD was diagnosed using the US fatty liver index. Trouble sleeping was diagnosed using a sleep disorder questionnaire. The correlation between trouble sleeping and the SII in NAFLD was investigated using multiple regression analysis, subgroup stratification, interaction tests, and restricted cubic spline, and the presence or absence of additive or multiplicative interactions was determined. Additionally, mediation analyses were performed to explore the role of the SII in mediating the effects of trouble sleeping on NAFLD. Results The survey included 10 963 participants. Multivariate logistic regression revealed that SII (OR: 1.21, 95% CI 1.08-1.35) and trouble sleeping (OR: 1.24, 95% CI 1.05-1.47) were positively correlated with NAFLD. For NAFLD, an additive but not multiplicative interaction was noted between the SII and trouble sleeping. The SII partially mediated the association between trouble sleeping and NAFLD, accounting for approximately 3.11% of the total effect (95% CI 0.01-0.05). Conclusion The SII and trouble sleeping were independently correlated with NAFLD risk. Furthermore, a combined effect may exist between SII and trouble sleeping, which increases the risk of NAFLD.